Sustained release donepezil loaded PLGA microspheres for injection: Preparation, in vitro and in vivo study - Wenjia Guo; Peng Quan; Liang Fang; Dongmei Cun; Mingshi Yang (Elsevier, 2015)
The purpose of this study was to develop a PLGA microspheres-based donepezil (DP) formulation which was expected to sustain release of DP for one week with high encapsulation efficiency (EE). DP derived from donepezil hydrochloride was encapsulated in PLGA microspheres by the O/W emulsion-solvent evaporation method. The optimized formulation which avoided the crushing of microspheres during the preparation process was characterized in terms of particle size, morphology, drug loading and EE, physical state of DP in the matrix and in vitro and in vivo release behavior. DP microspheres were prepared successfully with average diameter of 30 µm, drug loading of 15.92 ± 0.31% and EE up to 78.79 ± 2.56%. Scanning electron microscope image showed it has integrated spherical shape with no drug crystal and porous on its surface. Differential scanning calorimetry and X-ray diffraction results suggested DP was in amorphous state or molecularly dispersed in microspheres. The Tg of PLGA was increased with the addition of DP. The release profile in vitro was characterized with slow but continuous release that lasted for about one week and fitted well with first-order model, which suggested the diffusion governing release mechanism. After single-dose administration of DP microspheres via subcutaneous injection in rats, the plasma concentration of DP reached peak concentration at 0.50 d, and then declined gradually, but was still detectable at 15 d. A good correlation between in vitro and in vivo data was obtained. The results suggest the potential use of DP microspheres for treatment of Alzheimer's disease over long periods.